2020
DOI: 10.1161/jaha.119.014564
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Frontal Brain Activity in Patients With Heart Failure Assessed by Near‐Infrared Spectroscopy

Abstract: Background The prevalence of depression and/or anxiety disorders is reported to be higher in patients with heart failure ( HF ) than in the general population, and patients with HF also have coexisting cognitive problems. Recently, the development of near‐infrared spectroscopy ( NIRS ) has enabled noninvasive measurements of regional cerebral blood volume and brain activity, in terms of cerebral oxyhemoglobin in the cerebral cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 66 publications
2
10
0
1
Order By: Relevance
“…26 This study also showed that frontal brain activity assessed by NIRS reduced and was associated with high anxiety status and low cognitive function in patients with HF. 26 Further investigation to elucidate underlying pathological processes of associations between cardiac function to neurodegeneration during MI. Kresge et al performed a correlation analysis between LVEF t-tau and p-tau (biomarkers for Alzheimer's disease) in older adults (age ≥ 60 years).…”
Section: Cognitive Impairment and Hf: Clinical Reportssupporting
confidence: 52%
See 4 more Smart Citations
“…26 This study also showed that frontal brain activity assessed by NIRS reduced and was associated with high anxiety status and low cognitive function in patients with HF. 26 Further investigation to elucidate underlying pathological processes of associations between cardiac function to neurodegeneration during MI. Kresge et al performed a correlation analysis between LVEF t-tau and p-tau (biomarkers for Alzheimer's disease) in older adults (age ≥ 60 years).…”
Section: Cognitive Impairment and Hf: Clinical Reportssupporting
confidence: 52%
“…28 Furthermore, several studies had a limitation in the number of patients, an increased number of participants may be the best representation in the general population. 5,26,28 All of these findings suggest that the exact molecular mechanisms underlying cognitive impairment in HF is still a gap of knowledge from both preclinical and clinical studies.…”
Section: Impairment (Mci)mentioning
confidence: 99%
See 3 more Smart Citations